DO RISK MANAGEMENT DISCLOSURE AFFECT FIRM VALUE THROUGH PROFITABILITY? (Accounting Study Program, Universitas Ciputra Surabaya, 2022)
Investors are parties who determine a company’s sustainability because the funds invested by investors are a source of funds for the company. Investors do not only consider financial statements but also the nonfinancial side, namely the value of a company and how the company manages risk. The company’s value can be seen from the fair market value of the share price. If the stock price of a company is high, the value of the company is also high, thereby increasing investor confidence in investing. Therefore, this study examines the effect of enterprise risk management disclosures on firm value through profitability. The design of this research is quantitative research with hypothesis testing. The population in this study are banking companies listed on the Indonesia Stock Exchange from 2018 – 2020. The sampling technique used is purposive sampling so that a sample of 40 companies is obtained. The research period used is three years (2018 – 2020) which has total sample data is 120. The analytical method used is multiple linear regression using the SPSS version 23 application to process the data. The test results prove that the Company’s Risk Management Disclosure positively affects Firm Value and Profitability. While profitability does not affect firm value and does not have a significant impact on mediating the influence of corporate risk management on firm value. Keywords: enterprise risk management disclosure, firm value, profitability